VD_FINDINFO HC / 2011 / 156 vom 23. März 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, MINIMUM VITAL | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 276 CC, 2 al. 1 CL, 1 al. 1 LDIP, 308 al. 1 let. b CPC (CH), 405 al. 1 CPC (CH)